Early versus late oral feeding following total (pharyngo)laryngectomy: Systematic review and meta‐analysis. Issue 4 (4th February 2021) - Milinis, Kristijonas; Gaskell, Peter; Lau, Andrew; Lancaster, Jeffrey; Jones, Terry
Abstract: Timing of oral feeding following total laryngectomy is a contentious issue with highly varied practices. Multiple database search was performed to identify studies comparing outcomes of early (≤5 days) versus late (>5 days) oral feeding. Bias assessment was carried out using Cochrane bias tool. Random‐effects meta‐analysis was used. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The rate of pharyngocutaneous fistula (PCF) in randomized control trials (RCTs) in early versus late feeding was 15.2% versus 11.7% (RR 1.35, 95%CI [0.68–2.7], p = 0.40). The rate of PCF in the cohort studies was 14.1% versus 20.5% (RR 1.0, 95%CI [0.76–1.3], p = 0.98). The length of hospital stay was significantly shorter in the early feeding group (mean difference (days) −4.68 (−6.2 to −3.1, p < 0.0001). Early oral feeding appears to be safe and is associated with shorter hospital stay. However, the quality of evidence is low and the patient characteristics are not representative of current practices.